Resistance training for hypertensive elderly people: Literature review (Research, Society and Development, 2023)
Resistance training has been recommended as an important component in conditioning programs for the elderly, especially due to muscle losses, helping to increase muscle strength and power, reduce sarcopenia and improve functional capabilities in the elderly, and reduce BP. Therefore, the objective of this study was to analyze the impact of resistance training on blood pressure levels in hypertensive elderly people aged ≥ 50 years. The research methodology adopted was bibliographical research, of an exploratory nature. 10 articles published between 2018 and 2023 in the Scielo and Pudmed databases were analyzed, after applying inclusion and exclusion criteria. Promising data reveal a decrease in SBP and DBP after exercise (7), but others (3) have seen controversial effects. The post-exercise hypotensive effect is not 100% guaranteed for those who carry out the training. Because of this, it is important to carry out in-depth studies that take into account larger indicators to investigate possible measures that explain this variance in interventions.